The Effect of Der, Roa, Inflation on Corporate Values and Its Implications on Stock Prices (Case Study in Mining Sector Companies Listed in Indonesia Stock Exchange (2014- 2018 Period) - R. , Susanto Hendiarto (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to find out the description and how big the influence of debt-to-equity ratio (DER), return on assets (ROA), and inflation on company value and its implications on stock prices on mining sector companies listed on the Indonesia Stock Exchange Period 2008-2017, both simultaneously or partially. This study discusses three variables, namely DER, ROA, inflation as an independent or independent variable, company value as an intervening variable or between, and stock price as a dependent or dependent variable. The method used in this research is descriptive and verification methods with a quantitative approach, so the research method used is the descriptive survey method and the explanatory survey method. In this research object, there is a population frame. The technique taken is the purposive sampling technique. Types of data can be grouped into primary data and secondary data. Data collection techniques used are library research (library research) and field research (field research). By using eviews, the results show that DER, ROA, and inflation simultaneously influence the value of the company; partially DER has a significant effect on firm value, ROA has no effect and no significant effect on firm value, inflation has no effect and no significant effect on firm value, and the value of the company has no significant effect on stock prices. Based on this study, companies used as samples are still limited to companies registered in the mining sector, so further research needs to be done by using different research samples in a longer observation period so that it is expected that the results obtained can be generalized.